Role of Yoga Practices for Mental Health and Learning Habits of Management Students - Aryal, Lal Prasad (The Harvest, 2022)
Learning habit is purely and fairly psychological activity that needs sound mental health including inner-peace, calmness, easiness, positivity, curiosity, interest and self-motivation. The increased global interest in yoga practices in recent decades is primarily due to the expectancy that it can calm the mind and increase overall health and well-being of the students. Yoga provides training of mind and body to bring emotional and mental balance as well as it leads to alignment and harmony. This article discusses yoga (Asanas, Pranayamas and Dhyanas) as a potential tool for the management students to deal with mental health that essentially important for effective learning habits and to regulate themselves. This research study combination of both experimental and survey research designs. For this experimental study, 60 number of students are taken as sample who were failed in their mid-term examination and they were further classified as self-control group and experimental group with 30 students in each group in order to identify and confirm the effectiveness of yoga practices on academic performance of students. This study finding suggests that ‘yoga practices’ is an effective tool to solve mental health issues and finally it contributes for effective learning habits of management students. With this study, it is argued that students need such aid to listen inward, to their bodies, feelings, and ideas.